The effect of use of mobile communications to the human body - Beygam, N.; Tykezhanova, G.M.; Stashkevich, D.S. (Изд-во КарГУ, 2016)
This article contains information about the impact of mobile communicationson the human body. And also it considers the harmful of mobile phones to the human health. It is clear that electromagnetic radiation from mobile phones has a negative impact on the physiological state and psyche of the person. Not following the rulesof using of mobile phones are doing a lot of damage to the health of people.
Ұялы байланыс құралдарды қолданудың адам ағзасына əсері
Влияние использования сотовой связи на организм человека
Keywords: mobile phone, pupils, burden and hazards, eye disease, respiratory disease, musculoskeletal disease, nerve disease